2010
DOI: 10.1016/j.yjmcc.2010.04.015
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of Na+/K+-ATPase function in caveolin-1 knockout cardiac fibroblasts

Abstract: Recent studies have demonstrated that the Na+/K+-ATPase is not only an ion pump, but also a membrane receptor that confers the ligand-like effects of cardiotonic steroids (CTS) such as ouabain on protein kinases and cell growth. Because CTS have been implicated in cardiac fibrosis, this study examined the role of caveolae in the regulation of Na+/K+-ATPase function and CTS signaling in cardiac fibroblasts. In cardiac fibroblasts prepared from wild-type and caveolin-1 knockout [Cav-1(−/−)] mice, we found that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
2
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 41 publications
3
35
2
2
Order By: Relevance
“…Surprisingly, as shown in Fig. 6A, total Na ϩ /K ϩ -ATPase activity in RPE microsomes measured at saturating concentrations of all ligands was enhanced in Cav-1 KO microsomes, as has been recently observed in cardiac fibroblasts from Cav-1 KO mice (74). The increased total activity in RPE could not be explained by increases in levels of Na ϩ /K ϩ -ATPase because Western blots from microsomal fractions indicated similar levels of enzyme (Fig.…”
Section: Effect Of Cav-1 Deletion On Nasupporting
confidence: 74%
See 1 more Smart Citation
“…Surprisingly, as shown in Fig. 6A, total Na ϩ /K ϩ -ATPase activity in RPE microsomes measured at saturating concentrations of all ligands was enhanced in Cav-1 KO microsomes, as has been recently observed in cardiac fibroblasts from Cav-1 KO mice (74). The increased total activity in RPE could not be explained by increases in levels of Na ϩ /K ϩ -ATPase because Western blots from microsomal fractions indicated similar levels of enzyme (Fig.…”
Section: Effect Of Cav-1 Deletion On Nasupporting
confidence: 74%
“…6). Surprisingly, V max was significantly higher in Cav-1 KO membranes, a finding recently observed in Cav-1 KO cardiac fibroblasts (74). These results indicate that the loss of Cav-1 affects Na ϩ /K ϩ ATPase activity, but we cannot yet determine whether this effect is due to disruption of a complex containing Cav-1 and the Na ϩ /K ϩ -ATPase or is due to indirect changes in either membrane composition or ion concentrations.…”
Section: Discussioncontrasting
confidence: 52%
“…It is not clear whether these effects are a direct result of ouabain inhibiting Na ϩ /K ϩ -ATPase pump function or inducing signal transduction cascades. It was suggested that acute effects (5-10 min) of CTSs require much higher concentrations (micromolar) than the long-term effects (hours to days; nanomolar) observed in the present study (Quintas et al, 2010).…”
contrasting
confidence: 54%
“…The laboratory of Zijian Xie made an important discovery by demonstrating that a population of non-ion-transporting and highaffinity Na C /K C ATPase resides in caveolae, forming a signaling complex with Src kinase (Pierre & Xie 2006). When cardiotonic steroids at low picomolar to nanomolar concentrations bind to Na C /K C ATPase in the caveolae, this activates Src, which in turn results in transactivation of EGFR and activation of the PI3K-Akt pathway, the Ras-Raf-ERK MAP kinase pathway, IP3R activation, and calcium oscillations, resulting in regulation of earlyresponse genes associated with cell growth, motility, and metabolic pathways (Peng et al 1996, Kometiani et al 1998, Contreras et al 1999, Aizman et al 2001, Abramowitz et al 2003, Dmitrieva & Doris 2003, Dong et al 2004, Khundmiri et al 2006, Liu & Askari 2006, Liu et al 2007a,b, 2011, Pierre et al 2008, Quintas et al 2010, Morrill et al 2012, Bai et al 2013, Wu et al 2013, Rincon-Heredia et al 2014.…”
Section: Namentioning
confidence: 99%